AI-integrated project-based learning for speaking skill development in ESP communication classes among information system students - Silvia Nanda Putri Erito; Nurhasanah Halim (Journal of English Language Learning, 2026)
The integration of artificial intelligence (AI) in language learning has recently gained increasing attention, particularly in English for Specific Purposes (ESP) classrooms. This study explored students’ perceptions and experiences toward AI-assisted project-based learning for speaking skills among Information System students. The research aimed to investigate how AI tools supported students’ speaking development, presentation preparation, confidence, and learning experiences during project-based ESP activities. This study employed a qualitative descriptive design using open-ended questionnaires distributed to 45 Information System students. The collected data were analyzed using thematic analysis adapted from Braun and Clarke (2006) to identify recurring themes and patterns related to students’ experiences, speaking development, and AI integration in project-based learning activities. The findings revealed that students generally had positive perceptions toward the integration of AI tools in ESP speaking activities. AI tools such as ChatGPT, Google Gemini, ELSA Speak were perceived as supportive learning assistants that helped students improve pronunciation, grammar, vocabulary, idea organization, and presentation preparation. In addition, project-based learning activities increased students’ confidence, reduced speaking anxiety, and provided meaningful opportunities for collaborative and independent speaking practice. The study also found that several students demonstrated critical awareness regarding responsible AI usage and the importance of independent thinking during the learning process. Overall, AI-assisted project-based learning can support both students’ readiness , students’ confidence, students’ need in idea development and creates a more interactive, supportive, and student-centered learning environment in ESP class for speaking activities that can positively contribute to ESP speaking development in higher education contexts